2020
DOI: 10.1136/bmjgh-2019-002020
|View full text |Cite
|
Sign up to set email alerts
|

The influence of distance and quality on utilisation of birthing services at health facilities in Eastern Region, Ghana

Abstract: ObjectivesSkilled birth attendance is the single most important intervention to reduce maternal mortality. However, studies have not used routinely collected health service birth data at named health facilities to understand the influence of distance and quality of care on childbirth service utilisation. Thus, this paper aims to quantify the influence of distance and quality of healthcare on utilisation of birthing services using routine health data in Eastern Region, Ghana.MethodsWe used a spatial interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 27 publications
3
51
0
Order By: Relevance
“…Consequently, higher health services utilization in rural locations is not always a function of improved healthcare delivery system but a reflection of lack of choice for better alternatives. Indeed, other barriers to MNCH service utilization not explored in this study are acknowledged in terms of long travel times to health facilities [24,26,29], socio-cultural beliefs [16,23,30,31] and financial inaccessibility [32][33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, higher health services utilization in rural locations is not always a function of improved healthcare delivery system but a reflection of lack of choice for better alternatives. Indeed, other barriers to MNCH service utilization not explored in this study are acknowledged in terms of long travel times to health facilities [24,26,29], socio-cultural beliefs [16,23,30,31] and financial inaccessibility [32][33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Density of midwives and other frontline health staff significantly correlated with number of ANC visits recorded in the study health facilities over the three-year period, contrary to findings by similar studies on Ghana [9,18,19] and other countries [20,21], which reported that the number of frontline health workers per se did not enhance utilization of maternal and child health services. These studies argue that poor attitudes of staff and other health system challenges remain important constraints to utilization of maternal, newborn and child health (MNCH) services in Ghana [16,[22][23][24][25][26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…The journey origin and health facility used were clearly defined, and geographic coordinates were available to measure proximity compared with limitations in similar studies [ 46 ]. We avoided the assumption in DHS survey data analysis that women use the health facility closest to their residence [ 12 ], as there is evidence of large variations in expected (nearest health facility) and observed patterns of using birthing services in health facilities [ 47 ]. Our geospatial analysis also eliminated errors associated with self-reported distance and recall bias in other studies [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The 2014 Ghana Demographic and Health Survey (GDHS) indicated that 74% of mothers living in rural areas were least probable to receive early postnatal check-up relative to other subgroups. Women in rural areas of Ghana travel 4 km more than urban women to reach a hospital [ 17 ]. The same study indicated that a kilometre increase in distance significantly reduces maternal healthcare utilisation [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Women in rural areas of Ghana travel 4 km more than urban women to reach a hospital [17]. The same study indicated that a kilometre increase in distance significantly reduces maternal healthcare utilisation [17]. Additionally, it is known that the distribution of health facilities is skewed towards urban centres in Ghana [18].…”
Section: Introductionmentioning
confidence: 99%